Perbedaan Kemampuan Komunikasi Matematik Siswa Antara Yang Mendapatkan Model Pembelajaran Jigsaw Dan Cooperative Script: Studi Kuasi Eksperimen di salah satu SMPN yang ada di Banyuresmi - STKIP Garut Tahun 2012/2013) - Sulastri, Susi; Haq, Cici Nurul (Department of Mathematics Education Program IPI Garut, 2013)
This research is done because a lot of students who have difficulty in understanding the concepts of mathematics. Based formulation of the problem in this study, i.e. whether there is a difference between the students' mathematical communication skills are getting instructional model jigsaw premises cooperative script? . the study aims to determine differences in mathematical ability of communication between the students who get the Jigsaw cooperative learning model script. This research was conducted using a quasi-experimental. The instrument used to measure the communication skills of mathematics that is shaped in the form of a written test descriptions. Tests administered before researcher provide treatment (pretest) and after treatment (posttest), about the same as the pretest posttest questions. Based on data from the pretest and posttest results, both normal distribution and homogeneous so that data processing followed by t-test, thus Ho is accepted. The results of this study indicate that there is no difference between the students' mathematical communication skills that get the Jigsaw cooperative learning model script. Penelitian ini dilakukan karena banyak siswa mengalami kesulitan dalam memahami konsep-konsep matematika.Berdasarkan rumusan masalah dalam penelitian ini, yaitu “apakah terdapat perbedaan kemampuan komunikasi matematik siswa antara yang mendapatkan model pembelajaran Jigsaw dan Cooperative Script?”, maka penelitian ini bertujuan untuk mengetahui perbedaan kemampuan komunikasi matematik siswa antara yang mendapatkan model pembelajaran Jigsaw dengan Cooperative Script. Penelitian ini dilakukan dengan menggunakan metode quasi eksperimen.Berdasarkan data hasil pretest dan postest, keduanya berdistribusi normal dan homogen sehingga pengolahan data dilanjutkan dengan Uji t,dengan demikian Ho diterima. Hasil dari penelitian ini menunjukkan bahwa tidak terdapat perbedaan kemampuan komunikasi matematik siswa antara yang mendapatkan model pembelajaran Jigsaw dengan Cooperative Script.